Empower Edu Tour motivates 117 orang ssli kids in science and mathematics - UMP, PNC (2019)
The happiness can be clearly seen on the faces of 117 Orang Asli students from four primary schools around Pekan and Bera when they participate in the Empower Edu-Tour Programme at the Pahang Public Library on November 20, 2019.